Maqāṣid al-Qurʾān Perspektif Ṭāhā Jābir al-ʿAlwānī dan Implikasinya bagi Kajian Tafsīr Maqāṣidī di Indonesia - Wildah, Wildah Nurul Islami (Asosiasi Ilmu Alquran dan Tafsir se-Indonesia, 2023)
The examination of maqāṣid al-qur'ān serves as the foundation for the interpretation of Qur'anic verses that are directed towards the welfare and advantage of humanity. During the classical era, mufasirs frequently interpreted the Qur'anic verses in a manner that aligned with their theological doctrines, rather than adhering to the universal intent of the revealed verses. In contemporary times, the utilisation of the maqāṣid al-qur'ān approach has become prevalent as a means to mitigate the issue of subjective interpretation in various products. The study conducted by Al-'Alwānī on maqāṣid al-qur'ān holds significant importance in uncovering the universal objectives embedded within the Qur'ānic verses that remain veiled within the text. The present study centres its attention on the subsequent problem formulation: What is the methodology employed by Ṭāhā Jābir Al-'Alwānī in the examination of maqāṣid al-qur'ān, and how does the maqāṣid al-qur'ān methodology developed by Al-'Alwānī find practical application in the interpretation of verses within the Qur'an? What are the implications of Al-'Alwānī's maqāṣid al-qur'ān method for the study of tafsīr maqāṣidi in Indonesia? This study employs a qualitative descriptive approach to conduct library research, aiming to provide a comprehensive description and analysis of the collected data. The findings of this study demonstrate that Al-'Alwānī's ideas are grounded in the al-manhaj al-qur'ānī paradigm, which aims to develop the concept of al-Maqāṣid al-Qur'āniyyah al-'Ulyā al-Ḥakimah. This concept encompasses three fundamental principles found in the Qur'an: al-tawḥīd, al-tazkiyah, and al-'umrān. From a practical standpoint, it is possible to situate al-Maqāṣid al-Qur'āniyyah al-'Ulyā al-Ḥākimah within various spheres of existence, encompassing but not limited to the realms of economics, politics, social dynamics, and other pertinent domains. By employing Al-'Alwānī's approach, which is grounded in the principles of al-tawḥīd, al-tazkiyyah, and al-'umrān, the objective of promoting the welfare of individuals can be achieved, encompassing the cultivation of religious moderation. The present study carries significant implications for the hermeneutical analysis of the Qur'an, specifically in relation to the application of maṣlahah (public interest) and the overarching universal intent of the verse, rather than focusing on the theological validity of the mufasir (Qur'anic commentator). The method proposed by Al-Alwānī also plays a significant role in the advancement of tafsīr maqāṣidī in Indonesia, a subject that has been extensively explored and expanded upon by Abdul Mustaqim.